Optimally-designed single fiber Bragg grating filter scheme for RZ-OOK/DPSK/DQPSK to NRZ-OOK/DPSK/DQPSK format conversion - Cao, Hui; Shu, Xuewen; Atai, Javid; Gbadebo, Adenowo; Xiong, Bangyun; Fan, Ting; Tang, HaiShu; Yang, Weili; Yu, Yu (Optics express, 2014)
We investigate return-to-zero (RZ) to non-return-to-zero (NRZ) format conversion by means of the linear time-invariant system theory. It is shown that the problem of converting random RZ stream to NRZ stream can be reduced to constructing an appropriate transfer function for the linear filter. This approach is then used to propose novel optimally-designed single fiber Bragg grating (FBG) filter scheme for RZ-OOK/DPSK/DQPSK to NRZ-OOK/DPSK/DQPSK format conversion. The spectral response of the FBG is designed according to the optical spectra of the algebraic difference between isolated NRZ and RZ pulses, and the filter order is optimized for the maximum Q-factor of the output NRZ signals. Experimental results as well as simulations show that such an optimally-designed FBG can successfully perform RZ-OOK/DPSK/DQPSK to NRZ-OOK/DPSK/DQPSK format conversion.